Alteration in gut microbiota accompanied by increased intestinal permeability and Tfh/Tfr imbalance in patients with active SLE - Xiaodi Chu; Shuya Li; Yueying Wang; Dazhen Guo; Nana Zhao; Yuanyuan Han; Qian Xing (Frontiers in Cellular and Infection Microbiology)
BackgroundIncreased intestinal permeability and altered intestinal microbiota may influence cytokine regulatory immunity in systemic lupus erythematosus (SLE). This study aimed to elucidate the relationship between intestinal flora alters and follicular helper T cells (Tfh), regulatory T cells (Treg) cells, and cytokines in SLE.MethodsIn total, 23 patients with active SLE (SLE-A group), 18 patients with stable SLE (SLE-nA group), and 24 healthy controls (HC group) were enrolled. Tfh, follicular T regulatory (Tfr), and Treg cells were measured by flow cytometry, and fecal samples were analyzed using 16S rRNA gene sequencing. The relationship between the gut microbiome and the SLE disease activity index (SLEDAI-2k), zonulin (an indicator of intestinal permeability), IL-2, IL-6, and IL-21 levels was analyzed.ResultsDecreased Treg cells and imbalanced Tfh/Tfr were associated with elevated disease activity in SLE-A group. The increase in zonulin levels in SLE-A group indicated worsened intestinal mucosal barrier damage, potentially linked with the increase in the dominant microflora Escherichia-Shigella. Furthermore, the increase in zonulin was correlated with a severe imbalance in Tfh/Tfr. Moreover, decreased IL-2 levels were associated with a decrease in Ruminococcus and may modulate the reduction in Treg cells during disease progression. Zonulin also exhibited a negative correlation with IL-2.ConclusionZonulin may be involved in the Tfh/Tfr immune imbalance in patients with SLE, and Faecalibacterium and Ruminococcus may contribute to disease development by regulating Treg cells and Tfh/Tfr imbalance. Taken together, these findings may provide new insights into the role of cytokines in the treatment of SLE.